Isolation and characterization of cDNA clones for plant cyclins. - Hata, S (1991)
We have isolated and sequenced a carrot cDNA and two soybean cDNAs encoding mitotic cyclin homologs. The soybean clones were derived from nearly identical cognate genes. The carrot cyclin and soybean cyclins were slightly more similar to A-type and B-type cyclins thus far defined, respectively. However, they had divergent amino acid sequences in the portion that is most highly conserved in known cyclins and we could not easily include them in either of the phylogenetic types. Since the homology between carrot and soybean cyclins was low, each of them might define a novel and distinct type. The mRNA of carrot cyclin, 1.5 kb in length, was expressed concomitant with somatic embryogenesis of cultured cells. Expression of soybean cyclin mRNAs, 1.6 kb in length, was localized in proliferating parts of seedlings. As in the case of cyclin genes of marine invertebrates, microinjection of a synthetic mRNA for the soybean cyclin induced the maturation of Xenopus oocytes. Other cyclin genes may be present because, on Southern blot analysis of soybean genomic DNA, the isolated soybean cDNA probe hybridized with additional genes under low stringency.